Early Modern Skepticism and the Origins of Toleration - Levine, Alan (Lexington Books, 1999)
This collection of original essays by the nation's leading political theorists examines the origins of modernity and considers the question of tolerance as a product of early modern religious skepticism. Rather than approaching the problem through a purely historical lens, the authors actively demonstrate the significance of these issues to contemporary debates in political philosophy and public policy. The contributors to Early Modern Skepticism raise and address questions of the utmost significance: Is religious faith necessary for ethical behavior? Is skepticism a fruitful ground from which to argue for toleration? This book will be of interest to historians, philosophers, religious scholars, and political theorists—anyone concerned about the tensions between private beliefs and public behavior.